2018
DOI: 10.1039/c8cc02880j
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal coordination of fused arenes to a Pd3 cluster site

Abstract: We report bimodal coordination behaviour of fused arenes at a Pd3 cluster site. A cyclooctatetraene-supported Pd3 cluster accommodates anthracene and tetracene in an oxidative π-addition manner, whereas triphenylene and fluoranthene are accommodated in a π-coordination manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Our group and others have shown that metal-sheet sandwich compounds [M x (CUH) 2 ] z ( x ≥ 3) are obtained as a class of bis-ligated, ligand-deficient sandwich compounds ( x > y = 2), where large carbocyclic rings such as Tr are used as the face-capping ligands. , During the reactivity study of [Pd 3 Tr 2 (CH 3 CN) 3 ]­[B­(Ar F ) 4 ] 2 ( 1 , Ar F = 3,5-(CF 3 ) 2 C 6 H 3 ), , we found that an organo-Pd 13 cluster can be produced; for example, attempted recrystallization of the methylated complex [Pd 3 Tr 2 (CH 3 CN) 2 (CH 3 )]­[B­(Ar F ) 4 ] ( 2 ), which was generated by treatment of 1 with CH 3 Li, gave a few black crystals of the homoleptic 13-atom Pd cluster [Pd 13 Tr 6 ]­[B­(Ar F ) 4 ] 2 ( 3 ). Unfortunately, however, this method gave only traces of 3 (<1% yield) with poor reproducibility.…”
mentioning
confidence: 99%
“…Our group and others have shown that metal-sheet sandwich compounds [M x (CUH) 2 ] z ( x ≥ 3) are obtained as a class of bis-ligated, ligand-deficient sandwich compounds ( x > y = 2), where large carbocyclic rings such as Tr are used as the face-capping ligands. , During the reactivity study of [Pd 3 Tr 2 (CH 3 CN) 3 ]­[B­(Ar F ) 4 ] 2 ( 1 , Ar F = 3,5-(CF 3 ) 2 C 6 H 3 ), , we found that an organo-Pd 13 cluster can be produced; for example, attempted recrystallization of the methylated complex [Pd 3 Tr 2 (CH 3 CN) 2 (CH 3 )]­[B­(Ar F ) 4 ] ( 2 ), which was generated by treatment of 1 with CH 3 Li, gave a few black crystals of the homoleptic 13-atom Pd cluster [Pd 13 Tr 6 ]­[B­(Ar F ) 4 ] 2 ( 3 ). Unfortunately, however, this method gave only traces of 3 (<1% yield) with poor reproducibility.…”
mentioning
confidence: 99%
“…58,61–63 Murahashi and co-workers have reported several sandwich-type complexes with Pd 3 to Pd 5 clusters bridging two hydrocarbon rings. 64–68 However, for σ-bonded polymetalated derivatives of benzene, the only examples with Pd are those reported by our group, 39–41 plus the 3-fold cyclopalladation of a 1,3,5-tris(di-2-pyridylamino)benzene ring. 69 There is also a report of a tripalladated arylamine and a tetrapalladated pyrene, obtained by mechanochemical solvent-free oxidative addition of aryl halides to a Pd(0) complex.…”
Section: Introductionmentioning
confidence: 84%
“…Acenaphthylene-COT-Pd 4 sandwich complexes Next, we examined the arene-exchange reaction of the triangular Pd 3 cluster [Pd 3 (μ 3 -anisole)(μ 3 -COT)(CH 3 CN) 3 ][PF 6 ] 2 (2) which shows a high μ 3 -arene exchange reactivity. [10][11][12] The reaction of 2 with acenaphthylene (5 equiv.) proceeded at 60 °C, giving the Pd 4 sheet cluster [Pd 4 (μ 4 -acenaphthylene)(μ 4 -COT) (CH 3 CN) 2 ][PF 6 ] 2 (3), where an additional Pd 0 atom incorporated into the sandwich framework was generated probably through decomposition of a portion of the starting complex 2.…”
Section: Bis(acenaphthylene)-pd 3 Sandwich Complexesmentioning
confidence: 99%
“…9 The multiple metal binding of several other fused arenes including naphthalene and anthracene have also been identified. 4d, [10][11][12] Through these studies, it has been proposed that the μ 3 -or higher order bridging coordination of fused arenes are classified by the following two modes; (i) the π-coordination mode involving only even hapto-numbers such as η 2 for binding of each metal, and (ii) the oxidative π-addition involving odd hapto-numbers such as η 3 in addition to η 2 for metal binding. 4d,11 In the course of our continuing investigation on the multiple metal binding ability of fused arenes, here we focused on acenaphthylene, whose coordination has been dominated by the oxidative π-addition mode, presumably because of the propensity to bind a metal atom at its five-membered cyclopentadienyl-like substructure.…”
Section: Introductionmentioning
confidence: 99%